Advances in Human Factors and Ergonomics in Healthcare and Medical Devices Proceedings of the AHFE 2017 International Conferences on Human Factors and Ergonomics in Healthcare and Medical Devices, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Duffy, Vincent; Lightner, Nancy (Advances in Intelligent Systems and Computing,, 2018)
This book discusses the latest advances in human factors and ergonomics, focusing on methods for improving quality, safety, efficiency, and effectiveness in patient care. By emphasizing the physical, cognitive, and organizational aspects of human factors and ergonomics applications, it presents various perspectives, including those of clinicians, patients, health organizations, and insurance providers. The book describes cutting-edge applications, highlighting best practices for staff interactions with patients, as well as interactions with computers and medical devices. It also presents new findings related to improved organizational outcomes in healthcare settings, and approaches to modeling and analysis specifically targeting those work aspects unique to healthcare. Based on the AHFE 2017 International Conference on Human Factors and Ergonomics in Healthcare and Medical Devices, held on July 17-21, 2017, in Los Angeles, California, USA, the book is intended as a timely reference guide for both researchers involved in the design of healthcare systems and devices and for healthcare professionals working to deliver safe and effective health service. Moreover, by providing a useful survey of cutting-edge methods for improving organizational outcomes in healthcare settings, the book also represents a source of inspiration for healthcare counselors and international health organizations.